Hydrologic Regime Determines Catchment‐Scale Dissolved Carbon Export Patterns - Li, Xiao; Wang, Jian; Yin, Wei; Xu, Jianfeng; Xiao, Haibing; Zhao, Hongying; Shi, Yongyong; Wang, Lei; Hao, Rui; Li, Haiyan; Huang, Yiming; Jiang, Hai; et al. (Water resources research, 2025)
Hydrologic regimes are affecting terrestrial carbon transformation, chemical weathering and lateral transport. However, its impacts on dissolved carbon export patterns remains elusive. In this study, we collected a 2‐year high‐frequency dissolved inorganic (DIC) and organic carbon (DOC) dataset, namely a wet year (Rainfall = 1,158 mm) and a dry year (Rainfall = 603 mm). The results showed that drought led to a significant decrease in dissolved carbon concentration and discharge during the monitoring period. During non‐storm periods, DIC and DOC shifted from dilution and chemostatic to enrichment patterns from wet to dry years, respectively. However, the export patterns were reversed during storm periods. DIC and DOC export patterns in wet year were dominated by dilution and chemostatic, respectively, while both patterns were dominated by dilution in dry year. Structural equation models revealed that the aridity index and temperature may affect dissolved carbon export patterns. We further classified storm events into three major types and conceptualized catchment‐scale transport mechanisms for dissolved carbon. Dry‐AMCs events result in DIC dilution and DOC chemostatic behavior, whereas Wet‐AMCs events result in DIC chemostatic and DOC enrichment behavior due to increased hydrological connectivity. The third type corresponds to extreme events, where larger overland flow often results in DIC dilution but DOC enrichment behavior. These findings reveal the predominant role of drought in altering carbon lateral export by decreasing concentrations and fluxes and modifying export patterns. Key Points Dissolved carbon concentrations decreased significantly from a wet year to a dry year Drought caused dissolved carbon to be diluted during storm periods and enriched during non‐storm periods Seasonality and event characteristics jointly influence dissolved carbon export patterns